Examining the Intention to Use Mobile Health Applications Amongst Indonesians - Gabriela Amanda; Chrisanty V. Layman (Universitas Pelita Harapan, 2022)
The use of m-health applications in Indonesia is currently increasing drastically during the COVID-19 pandemic. This has led to intense competition between companies providing health application services to continue to retain users, one of which is by understanding the important factors that influence the intention to use applications either directly or indirectly, apart from the COVID-19 pandemic. This study aims to examine the effect of quality application, perceived information quality, trust, perceived usefulness and intention to use. The data employed for this study were collected from 150 users of mobile health applications in Indonesia. Hypothesis testing in this study used the Structural Equation Modelling (SEM) for the statistical analysis method. The results of this study indicate that application quality has a positive effect on perceived information quality, perceived information quality has a positive effect on trust, trust has a positive effect on perceived usefulness, and perceived usefulness has a positive effect on intention to use. Finally, the managerial implications in this study are expected to be a source of thought, especially for companies in the health technology industry to continue to improve and evaluate the quality of application that indirectly affect intention to use.